Poetic conventions in an Old-Babylonian hymn to I tar - Prinsloo, G. T. M. (Journal for semitics, 1992)
A general shortcoming in analyses of Akkadian texts is the tendency to restrict such undertakings to translations and philological notes. Only rarely is sufficient attention paid to detailed literary analysis of these texts. This shortcoming is especially apparent in the case of poetic texts. It is generally accepted that a number of specialised techniques, which playa major role in the interpretation, occur in poems. However, comprehensive analyses of poetic techniques in Akkadian poems are virtually non-existent. The aim of this paper is to provide a comprehensive poetic analysis of an Old-Babylonian hymn to Itar. Close attention is paid to the function of various poetic techniques on different levels of the text. The conclusion is reached that the interplay between these techniques should be taken into account when the poem is interpreted. The creating of patterns is found to be the dominant textual strategy in the poem.